Let us be influenced but not dominated by the West: students’ perspectives on social work development in India - Rajendra Baikady; Cheng Shengli (Journal of Social Work Education and Practice, 2023)
Despite decades of practice and development, social work education in India is still Western-centric. Social work in India is still not well recognised: it does not have an accrediting body or professional recognition within the country. This study gives voice to a sample of social work students regarding some of the challenges they face, including the curriculum, pedagogy, recognition of the profession and the practicum. The study is based on interviews with students from five universities in India and includes concrete recommendations for improving the professional training of social work students.